Political correctness and freedom of expression - Embling, Geoffrey (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2017)
A brief history of political correctness is discussed along with various definitions of it, ranging from political correctness being a benign attempt to prevent offense and avert discrimination to stronger views equating it with Communist censorship or branding it as "cultural Marxism". The aim of the research is to discover what political correctness is, how it relates to freedom of expression and what wider implications and effects it has on society. The moral foundations of rights and free speech in particular are introduced in order to set a framework to determine what authority people and governments have to censor others' expression. Different philosophical views on the limits of free speech are discussed, and arguments for and against hate speech are analysed and related to political correctness. The thesis looks at political correctness on university campuses, which involves speech codes, antidiscrimination legislation and changing the Western canon to a more multicultural syllabus. The recent South African university protests involving issues such as white privilege, university fees and rape are discussed and related to political correctness. The thesis examines the role of political correctness in the censorship of humour, it discusses the historical role of satire in challenging dogmatism and it looks at the psychology behind intolerance. Political correctness appeals to tolerance, which is sometimes elevated at the expense of truth. Truth and tolerance are therefore weighed up, along with their altered definitions in today's relativistic society. The last part of the thesis looks at South Africa's unique brand of political correctness, along with Black Economic Empowerment, colonialism and white guilt, and the research concludes that political correctness is a distinct form of censorship which has developed in modern democracies. The new forms of justice and morality seen in political correctness are distortions of left-wing liberalism, which appeal to different values to those of traditional liberalism.
Keywords: Political correctness; Freedom of speech; Political correctness -- South Africa; Freedom of speech -- South Africa; Censorship; Censorship -- South Africa; South Africa -- Politics and government; Political satire, -- South African; Fanatacism; Toleration